Study on Posterior Interventricular Artery in Post Mortem Heart of Adult Bangladeshi Peopl - Hussain, Md Asad; Nahar, Anjuman; Hakim, Md Monjurul; Ara, Shamim (Journal of Chittagong Medical College Teachers’ Association, 2012)
Context: Heart diseases are the predominant cause of disability and death in Bangladesh. Treatment of heart disease is costly & complex issue. The study of the posterior interventricular artery is essential for the proper diagnosis and treatment of the heart diseases. Study design: Descriptive type. Place & period of study: The study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka from February 2005 to January 2006. Materials: The present study was performed on sixty (60) adult postmortem human hearts of Bangladeshi people aging from 20 to 75 years. The hearts were collected from unclaimed dead bodies autopsied in the morgue of Dhaka Medical College. Methods: The samples were divided into 3 age groups-Group A (20 to 40 years) consists of 35 males & 7 female samplex, Group B (41 to 60 years) consists of 8 male & 3 female samples and Group C (61 to 75 years) consists of 7 male samples. All the samples of different age groups were examined gross morphologically. Results : The posterior interventricular artery arised from the right coronary artery 90% & from the left coronary artery 10% and was terminated in the distal half of the posterior interventricular groove 67%. Conclusion: The results of the present study can be helpful to the cardiologists and cardiovascular surgeons in the proper diagnosis and management of the heart diseases. JCMCTA 2011; 22(2): 22-26